Who’s under the mask? Colourdifferentiated identification labels for perioperative staff - Diana Bentley (Journal of Perioperative Nursing)
Staff identification in the perioperative environment is difficult when all staff, students and visitors wear the same attire. All attire needs to be laundered to national standards for infection control governance and consequently attire cannot be individualised. In emergency situations it is also difficult to identify the roles of all staff with standard methods of identification.